Direction Given Under the Magistrates' Courts and County Court Appeals (Criminal Legal Aid) (Costs) Rules (Northern Ireland) 2009 : Interim Payments in Criminal Cases in the Magistrates' Courts and County Courts.: Interim Payments in Criminal Cases in the Magistrates' Courts and County Courts. ([2017]) - Northern Ireland., Department of Justice,
No abstract available